Business Owners and Income-Shifting between Tax Bases: Empirical Evidence from a Finnish Tax Reform - Jarkko Harju; Tuomas Matikka (Center for Economic Studies and ifo Institute (CESifo), 2014)
This study examines the extent of income-shifting between tax bases among the owners of privately held businesses. The dual income tax system in Finland offers noticeable incentives for income-shifting between wages and dividends for business owners. The dividend tax reform of 2005 enables us to study how this particular form of tax avoidance reacts to an exogenous change in tax rates. Our results support highly active income-shifting behavior. We find that the income-shifting effect is homogeneous across different owners and firms. However, we find that the size of the tax incentive affects the size of the response, indicating that costs related to income-shifting are important.
Keywords: H24; H25; H32; 330; business owners; income-shifting; income taxation